2nd International congress on pedagogical mediation in language learning - Gómez Sáenz, Cenaida; Martínez Verdugo, Diana Liceth; Acosta López, Juan Carlos (Memorias, 2023)
The 2nd International Congress on Pedagogical Mediation in Language Learning "New strategies towards language acquisition and learning", was held virtually on June 8th and 9th, 2023. The primary aim was to establish a platform for meaningful exchange and thoughtful contemplation on the most recent trends, strategies, and tools in pedagogical mediation. These advancements are instrumental in enhancing the overall standard of instruction and language acquisition, both for native and foreign languages, while concurrently fostering linguistic and cultural diversity within an increasingly globalized context. The congress was aimed at undergraduate and postgraduate students, teachers, and researchers, who could exchange ideas, knowledge, and experiences in pedagogical mediation. Attendees had the opportunity to learn about the latest trends in language teaching and tools and techniques to enhance student learning. The importance of these types of congresses lies in the fact that pedagogical mediation can significantly improve the quality of language teaching. Teachers can use pedagogical mediation to adapt their teaching to the needs of students. In contrast, students can learn autonomously and develop metacognitive skills that allow them to reflect on their own learning process.